2017
DOI: 10.1126/science.aam6383
|View full text |Cite
|
Sign up to set email alerts
|

A dedicated network for social interaction processing in the primate brain

Abstract: Primate cognition requires interaction processing. Interactions can reveal otherwise hidden properties of intentional agents, such as thoughts and feelings, and of inanimate objects, such as mass and material. Where and how interaction analyses are implemented in the brain is unknown. Using whole-brain functional magnetic resonance imaging in macaque monkeys, we discovered a network centered in the medial and ventrolateral prefrontal cortex that is exclusively engaged in social interaction analysis. Exclusivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
206
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(270 citation statements)
references
References 51 publications
30
206
0
1
Order By: Relevance
“…This hypothesis is supported by recent fMRI data from monkeys engaged in the visual processing of interactions (Sliwa & Freiwald, ), in which planned contrasts allowed to ascribe the recruitment of classical visuomotor areas to the decoding of agents' actions. Instead, medial prefrontal regions displayed a selective response to interactions.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This hypothesis is supported by recent fMRI data from monkeys engaged in the visual processing of interactions (Sliwa & Freiwald, ), in which planned contrasts allowed to ascribe the recruitment of classical visuomotor areas to the decoding of agents' actions. Instead, medial prefrontal regions displayed a selective response to interactions.…”
Section: Discussionmentioning
confidence: 56%
“…Instead, medial prefrontal regions displayed a selective response to interactions. The spatial overlap between these regions and the human mentalizing network suggested a role for such “ exclusively social interaction network ” in drawing inferences about the intentional states underlying the observed interactions, which in turn might have represented a potential evolutionary pressure to the development of mentalizing skills (Sliwa & Freiwald, ). We thus assessed whether available evidence from published studies supports the existence of “ exclusively social ” brain activations also in the human brain, or rather the neural processing of interactions can be reduced to the joint engagement of the mirror and mentalizing networks.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a recent study in macaques found regions of the frontal and parietal cortex that responded exclusively to movies of monkey social interactions and not to movies of monkeys conducting independent actions or of interactions between inanimate objects (4). If humans have a similarly selective cortical response to social interactions, where might it be found in the brain?…”
Section: E114 | Wwwpnasorgmentioning
confidence: 99%
“…We see not just agents and objects, but also agents interacting with each other. The ability to perceive and understand social interactions arises early in development (1) and is shared with other primates (2)(3)(4). Although considerable evidence has implicated particular brain regions in perceiving the characteristics of individual agents-including their age, sex, emotions, actions, thoughts, and direction of attention-whether specific regions in the human brain are systematically engaged in the perception of third-party social interactions is unknown.…”
Section: E114 | Wwwpnasorgmentioning
confidence: 99%
“…There is evidence of this mechanism in brain scans of primates (Sliwa and Freiwald, 2017) and human infants (de Haan andNelson, 1999, Southgate et al, 2008), and from human in utero behavioral experiments (Reid et al, 2017). This mechanism would plausibly underpin the fundamentality of social cooperation to human cognition (Barrett et al, 2010, Cortina andLiotti, 2010); a related point has been made about language, noting the fundamentality of dialog from which monolog is derived (Pickering and Garrod, 2004).…”
Section: Generalized Affordance Theorymentioning
confidence: 99%